Pendekatan Konseling Analisis Transaksional untuk Mengembangkan Kesadaran Diri Remaja - Mualwi Widiatmoko; Fadhila Malasari Ardini (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
The background of this study is the fact of less self-monitoring ability optimalization among adolescents, and as a result the lack of self-awareness among adolescents. The purpose of this study was to evaluate the effectiveness of transactional analysis in counseling approach to develop adolescent’s self-awareness. This study uses quasi experiment with non-equivalent pretest and posttest control group design. Population of this study are 20 students of class 11th in SMA Negeri 2 Ogan Ogan Ulu (OKU) grouped in the experimental group (10 students) and control group (10 students). Data were analyzed using non-parametric statistic with Mann Whitney or U-test. As a result of this study, the self-awareness profile picture in 11th grade students of senior high school in OKU has categorized in intermediate level, the design of transactional analysis counseling intervention, and transactional analysis counseling is effective to improve students’ self-awareness. Recommendation based on research for guidance and counseling teacher is to apply the procedure of transactional analysis counseling by using structural technique with aim to develop self-awareness of students, and next researcher is for exploration toward one of techniques in transactional analysis counseling to facilitate all indicators, aspects, and self-awareness dimention.